2014
DOI: 10.1088/2041-8205/790/2/l29
|View full text |Cite
|
Sign up to set email alerts
|

Observations of Subarcsecond Bright Dots in the Transition Region Above Sunspots With the Interface Region Imaging Spectrograph

Abstract: Observations with the Interface Region Imaging Spectrograph (IRIS) have revealed numerous sub-arcsecond bright dots in the transition region above sunspots. These bright dots are seen in the 1400Å and 1330Å slit-jaw images. They are clearly present in all sunspots we investigated, mostly in the penumbrae, but also occasionally in some umbrae and light bridges. The bright dots in the penumbrae typically appear slightly elongated, with the two dimensions being 300-600 km and 250-450 km, respectively. The long si… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
111
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(124 citation statements)
references
References 37 publications
13
111
0
Order By: Relevance
“…The bright dots are shortlived (25 s) and appear at the footpoints of large-scale coronal loops. Tian et al (2014a) found similar subarcsecond bright dots above sunspots in the transition region (TR) with the observations of the Interface Region Imaging Spectrograph (IRIS;De Pontieu et al 2014).…”
Section: Introductionsupporting
confidence: 70%
“…The bright dots are shortlived (25 s) and appear at the footpoints of large-scale coronal loops. Tian et al (2014a) found similar subarcsecond bright dots above sunspots in the transition region (TR) with the observations of the Interface Region Imaging Spectrograph (IRIS;De Pontieu et al 2014).…”
Section: Introductionsupporting
confidence: 70%
“…Recently, Tian et al (2014) reported on IRIS observations of bright dots in sunspots, the majority of which were observed in the penumbrae. The dot-like brightenings in their Si IV slit-jaw images appear to have properties similar to the PMJs in our data: they have similar small round shapes, lifetimes on the order of a minute, and those that show proper motion have comparable speeds of 10-40 km s −1 (our PMJs fall on the lower end of that range).…”
Section: Discussionmentioning
confidence: 99%
“…Those inside penumbrae are more compact, isolated, and ephemeral. In this study, we only focus on the subarcsecond and short-lived BDs within the penumbral area studied by Tian et al (2014b).…”
Section: Discussionmentioning
confidence: 99%
“…The recently launched Interface Region Imaging Spectrograph (IRIS; De Pontieu et al 2014) mission provides unprecedented observations of the solar TR and chromosphere with high cadence (several seconds), high spatial (0 167 pixel −1 ), and spectral resolution. Using IRIS 1400 and 1330 Å slit-jaw images (SJIs), Tian et al (2014b) revealed numerous short-lived subarcsecond bright dots (BDs) in the TR above every sunspot they investigated (located mainly in the penumbrae). These TR penumbral BDs often have intensities that are a few times stronger than their surrounding background in the 1400 Å SJIs.…”
Section: Introductionmentioning
confidence: 99%